2009
DOI: 10.1292/jvms.71.1053
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Profiles of Feline Breeds in Japan

Abstract: ABSTRACT. To clarify the behavioral profiles of 9 feline purebreds, 2 Persian subbreeds and the Japanese domestic cat, a questionnaire survey was distributed to 67 small-animal veterinarians. We found significant differences among breeds in all behavioral traits examined except for "inappropriate elimination". In addition, sexual differences were observed in certain behaviors, including "aggression toward cats", "general activity", "novelty-seeking", and "excitability". These behaviors were more common in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
18
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 15 publications
11
18
4
1
Order By: Relevance
“…Proportional morbidity for aggression to familiar cats was lower amongst cats in breed group 1 (Persian et al) those in breed group 4 (companion cats). Veterinarians in Japan have classified Persians as less aggressive to other cats than most other cat breeds there (Takeuchi and Morio 2009). Bamberger and Houpt (2006) found Siamese cats (in our study grouped in breed group 2) were predisposed to behave more aggressively, and domestic shorthairs (in our study grouped in breed group 4) tended to behave less aggressively in the…”
Section: Accepted Manuscriptmentioning
confidence: 47%
“…Proportional morbidity for aggression to familiar cats was lower amongst cats in breed group 1 (Persian et al) those in breed group 4 (companion cats). Veterinarians in Japan have classified Persians as less aggressive to other cats than most other cat breeds there (Takeuchi and Morio 2009). Bamberger and Houpt (2006) found Siamese cats (in our study grouped in breed group 2) were predisposed to behave more aggressively, and domestic shorthairs (in our study grouped in breed group 4) tended to behave less aggressively in the…”
Section: Accepted Manuscriptmentioning
confidence: 47%
“…Some previous studies have described breed-specific personality traits as reported by veterinarians and owners in response to questionnaires. Takeuchi and Mori (2009) reported that Japanese domestic cats (mongrel cats) and American Shorthair cats ranked higher on friendliness, playfulness, demand for affection, and novelty seeking than 10 other pure breeds examined in the study, whereas Chinchilla cats were ranked highest on aggression to humans and cats, timidity, and nervousness. Wilhelmy et al (2016) examined the links between appearance (e.g., coat color) and personality, but concluded that most individual differences stemmed from breed differences.…”
Section: Introductionmentioning
confidence: 72%
“…Taken together with the first finding, mongrel cats tended to have longer alleles in MS3 and MS4 than purebred cats, and those with longer alleles scored higher on Friendliness ( Figures 2B,C ). Takeuchi and Mori (2009) reported that Friendliness in Japanese domestic cats (mongrel cats) scored higher than in any other purebred cats examined. Our reports were consistent with their study; however, the functional reasons for the association for MS3 and MS4 were beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 91%
“…A osteoartrite progressiva pode prejudicar até mesmo a socialização destes animais que tendem a se manter deitados e são caracterizados como animais de baixa vivacidade (Graeme, 2000;Chang et al, 2007;Takeuchi & Mori, 2009;Inoue et al, 2016).…”
Section: Discussionunclassified